(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the diagnostic value of diffusion-weighted magnetic resonance imaging in detecting seminal vesicle invasion in prostate cancer. Methods: A cross-sectional descriptive study was conducted on 56 patients presenting to Military Hospital 103 between January 2023 and December 2024 who were diagnosed with prostate cancer. The diagnosis was confirmed by transrectal ultrasound-guided biopsy or histopathological examination following radical prostatectomy. All patients underwent pre-treatment prostate magnetic resonance imaging with a standardized protocol, including T2W and DWI/ADC sequences. MinADC values were measured at regions of interest corresponding to suspected seminal vesicle invasion. Histopathological results served as the reference standard for the assessment of invasion. Results: The average age of the study patients was 68.7, and the average PSA value was 38.6 ng/ml. 21 patients (37.5%) had seminal vesicle invasion confirmed on pathology, and 35 patients (62.5%) did not. The minADC value of lesions with seminal vesicle invasion was 0.601 ± 0.232 × 10-³ mm²/s, significantly lower than that of lesions without seminal vesicle invasion (1.016 ± 0.224 × 10-³ mm²/s), with p < 0.05. A minADC threshold of 0.835 × 10-³ mm²/s demonstrated a sensitivity of 90.5%, specificity of 85.7%, positive predictive value of 79.2%, negative predictive value of 93.8%, and diagnostic accuracy of 87.5%. The combination of T2W with both qualitative and quantitative DWI improved diagnostic accuracy for seminal vesicle invasion with 85.7% and 89.3%. Conclusion: Diffusion-weighted magnetic resonance imaging is a highly valuable imaging modality for diagnosing seminal vesicle invasion in patients with prostate cancer, particularly when combined with quantitative ADC values, which enhance diagnostic specificity and accuracy.